2012
DOI: 10.3758/s13415-012-0091-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social context and predictive relevance on action outcome monitoring

Abstract: Outcome monitoring is crucial for subsequent adjustments in behavior and is associated with a specific electrophysiological response, the feedback-related negativity (FRN). Besides feedback generated by one's own action, the performance of others may also be relevant for oneself, and the observation of outcomes for others' actions elicits an observer FRN (oFRN). To test how these components are influenced by social setting and predictive value of feedback information, we compared event-related potentials, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 110 publications
2
69
0
Order By: Relevance
“…The FRN is a scalp event-related potential (ERP) time-locked to the delivery of decision outcomes, and it is characterised by a larger negative-going deflection for non-rewards compared to rewards [12]. Evidence indicates that the FRN is linked to activity in medial frontal areas, and in particular the ACC [13][15]. This distinction between ERPs to positive and negative outcomes is now perceived as reflecting a fundamental ability to differentiate between valenced outcomes and has become the object of intense investigation [12], [16][23].…”
Section: Introductionmentioning
confidence: 99%
“…The FRN is a scalp event-related potential (ERP) time-locked to the delivery of decision outcomes, and it is characterised by a larger negative-going deflection for non-rewards compared to rewards [12]. Evidence indicates that the FRN is linked to activity in medial frontal areas, and in particular the ACC [13][15]. This distinction between ERPs to positive and negative outcomes is now perceived as reflecting a fundamental ability to differentiate between valenced outcomes and has become the object of intense investigation [12], [16][23].…”
Section: Introductionmentioning
confidence: 99%
“…As such, these studies, and others examining observational learning (Kozba, Thoma, Daum, & Bellebaum, 2011;Shane, Stevens, Harenski, & Kiehl, 2008), suggest that the medial-frontal reward system may underlie observational learning and, thus, is activated when people observe outcomes experienced by others. Furthermore, more recent work by Koban, Pourtois, Bediou, and Vuilleumier (2012) has further extended the observational learning literature by demonstrating that social context can also enhance or reduce the functional efficacy of the medial-frontal reward system. Specifically, Koban et al found that reward processing was enhanced when participants were in a cooperative, relative to a competitive, situation-a result suggesting that social context also influences reward evaluation by the medialfrontal system.…”
mentioning
confidence: 99%
“…The absence of strong agency effects might be related to the experimental setup, as we used an animated representation of a choice that had to be observed rather than asking participants to observe a real person performing the task. Indeed, many studies studying the observation of behavior used setups in which one participant observed another participant (e.g., de Bruijn, Ruissen, & Radke, ; Koban et al, ; van Schie, Mars, Coles, & Bekkering, ). In previous studies by our group, however, we reliably observed agency effects using designs comparable to the one applied in the present study (e.g., Bellebaum et al, ; Bellebaum & Colosio, ).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the electrophysiological correlates of feedback processing, effects on feedback‐locked ERPs were found for both delay and agency manipulations, with a larger FRN valence effect (more negative amplitudes for negative than positive feedback) for immediate compared to delayed feedback (Arbel, Hong, Baker, & Holroyd, ; Opitz, Ferdinand, & Mecklinger, ; Peterburs, Kobza, & Bellebaum, ; Weinberg, Luhmann, Bress, & Hajcak, ; Weismuller & Bellebaum, ; but see Wang, Chen, Lei, & Li, , for a negative finding) and for feedback given to active performers versus for observed persons (Bellebaum & Colosio, ; Bellebaum, Kobza, Thiele, & Daum, ; Koban, Pourtois, Bediou, & Vuilleumier, ). These findings suggest a reduced involvement of the striatum/ACC in feedback processing when feedback does not follow an own action immediately.…”
Section: Introductionmentioning
confidence: 99%